The Influence of Financial Attitude, Financial Management, Financial Knowledge, on Financial Satisfaction Of Accounting Students Feb Unud - Aulia Ayu Paramadina; I Ketut Yadnyana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the impact of financial attitude, financial management, and financial knowledge on financial satisfaction among Accounting students of the Faculty of Economics and Business, Udayana University. Given that students tend to spend money on lifestyle trends while showing limited interest in investing or saving, understanding the factors influencing their financial satisfaction is crucial. The research employs a quantitative approach using a survey method, with 213 questionnaires collected from active students through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that financial attitude, financial management, and financial knowledge have a positive and significant effect on financial satisfaction. These findings emphasize the importance of having a positive financial attitude, effective financial management skills, and a solid understanding of financial concepts in enhancing students' financial satisfaction. The study also suggests that fostering financial attitudes, skills, and knowledge early on can help students achieve long-term financial well-being in the future.